2020
DOI: 10.2147/ijn.s219042
|View full text |Cite
|
Sign up to set email alerts
|

<p>New Approaches in Breast Cancer Therapy Through Green Nanotechnology and Nano-Ayurvedic Medicine – Pre-Clinical and Pilot Human Clinical Investigations</p>

Abstract: The overarching objective of this investigation was to investigate the intervention of green nanotechnology to transform the ancient holistic Ayurvedic medicine scientifically credible through reproducible formulations and rigorous pre-clinical/clinical evaluations. Methods: We provide, herein, full details: (i) on the discovery and full characterization of gold nanoparticles-based Nano Swarna Bhasma (henceforth referred to as NSB drug); (ii) In vitro anti-tumor properties of NSB drug in breast tumor cells; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 66 publications
0
72
0
8
Order By: Relevance
“…Nano Swarna Bhasma (NSB), approved by the Indian government regulatory authority of AYUSH (DNA_SPN_B001_17), has been used in female patients with pathologically confirmed invasive breast cancer stage IIIA or IIIB and showed acceptable safety and excellent efficacy. 215 These studies provide strong evidence for the clinical potential of GNPs. However, as mentioned by the National Cancer Institute (NCI)-Radiation Therapy Oncology Group in translational program strategic guidelines for the early-stage development of radiosensitizers, the clinical transformation of any radiosensitizer is rarely a seamless transition directly from the bench to the bedside.…”
Section: Preclinical Studies Of Gnpsmentioning
confidence: 78%
“…Nano Swarna Bhasma (NSB), approved by the Indian government regulatory authority of AYUSH (DNA_SPN_B001_17), has been used in female patients with pathologically confirmed invasive breast cancer stage IIIA or IIIB and showed acceptable safety and excellent efficacy. 215 These studies provide strong evidence for the clinical potential of GNPs. However, as mentioned by the National Cancer Institute (NCI)-Radiation Therapy Oncology Group in translational program strategic guidelines for the early-stage development of radiosensitizers, the clinical transformation of any radiosensitizer is rarely a seamless transition directly from the bench to the bedside.…”
Section: Preclinical Studies Of Gnpsmentioning
confidence: 78%
“…The health benefits of MGF have prompted a rigorous research to find other sources of this valuable compound [ 4 , 5 ]. While the extracts from mango ( Mangifera indica L.) fruit peel [ 6 ], seeds, leaves [ 2 , 7 , 8 ], bark and roots [ 2 , 7 ] have been shown to contain this compound, MGF is also found abundantly in other plant species such as Salacia chinensis , Swertia chirata , Hypericum aucheri and Cyclopia intermedia [ 6 , 9 , 10 ]. The xanthones (MGF and isomangiferin) and flavanones (hesperitin and hesperidin) are the major components of C. intermedia extracts, and are thought to be responsible for most of its pharmacological effects, including anti-diabetic, anti-cancer, anti-obesity, antioxidant and antimicrobial activities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported on the use of green nanotechnology to synthesize AuNPs from M. indica L. [ 18 , 19 , 20 ] and MGF [ 6 , 9 ]. While MGF is a major phytochemical constituent of the peel of M. indica L., it is not known if MGF is involved in the synthesis of the AuNPs when synthesis is done using a plant extract.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of gold nano particles with Ayurvedic phytochemical herbs as cinnamon, curcumin, grape , mango….etc. led to innovative green nanoproduct called Nano-Ayurvedic formulations that will be a promising nanotechnology for cancer treatment (5) .…”
Section: Introductionmentioning
confidence: 99%